Therapeutic applications of Monte Carlo calculations in nuclear medicine - Zaidi, Habib (IOP, Institute of Physics, 2014)
Examines the applications of Monte Carlo (MC) calculations in therapeutic nuclear medicine, from basic principles to computer implementations of software packages and their applications in radiation dosimetry and treatment planning. This book covers the entire range of MC applications in therapeutic medical and health physics.